ANALISIS TENTANG PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP FUNGSI PARTAI POLITIK DI INDONESIA - Wiguna, Riyan; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by a political party functions that are the responsibility of political parties to run. Those functions such as; political communication, political socialization, political recruitment, political participation, articulation, aggregation and regulatory conflicts. So the authors take the title of the study "Analysis of Riau University Student Perception Functions Against Political Parties in Indonesia". The problem of this research is Riau University Student Perception How To Function Political Parties in Indonesia? The purpose of this study was to determine the perception of Riau University Students Against Functions Political Parties in Indonesia. The study population was a student of University of Riau, amounting to 27 268 people and a sample of 90 people. Data collection instruments which the questionnaire consists of 18 questions and the interview consisted of 18 questions. Analysis of data using qualitative descriptive analysis. The formulation of the hypothesis that the perception of students at the University of Riau on the functioning of political parties is good. These results indicate that the perception of students at the University of Riau on the functioning of political parties in Indonesia is good, this is indicated with a percentage of 62.04%, which is in the range of 50.01% -75% or categorized as "Good". So the hypotheses are accepted.Keywords:Perception, Political Party Function